High-Throughput Phytochemical Unscrambling of Flowers Originating from Astragalus membranaceus (Fisch.) Bge. var. mongholicus (Bge.) P. K. Hsiao and Astragalus membranaceus (Fisch.) Bug. by Applying the Intagretive Plant Metabolomics Method Using UHPLC−Q−TOF−MS/MS - Qi Liu; Jinghui Li; Meiling Gu; Wanying Kong; Zhao Lin; Jialin Mao; Meng Zhang; Liyan Jiang; Can Liu; Yumei Wang; Jicheng Liu (Molecules, 2023)
Astragalus membranaceus (Fisch.) Bge. var. mongholicus (Bge.) P. K. Hsiao (MO) and Astragalus membranaceus (Fisch.) Bug. (ME) are two primary sources of the Astragalus herb, also known as “Huangqi” in China, which is widely applied to treat hypertension, glomerulonephritis, ischemic heart disease, and diabetes mellitus. As two different sources of the Astragalus herb, the chemical profiles of MO and ME may be different. Previous studies showed abundant differences in chemical composition between MO and ME. Therefore, the by-products of MO and ME, such as Astragalus membranaceus (Fisch.) Bge. var. mongholicus (Bge.) P. K. Hsiao flower (MOF) and Astragalus membranaceus (Fisch.) Bug. flower (MEF), may have different phytochemical profiles. In this paper, a metabolomics method combined with ultra-high-performance liquid chromatography and electrospray ionization/quadrupole time-of-flight mass spectrometry (UHPLC−Q−TOF−MS/MS) was employed to analyze the components of MOF and MEF. Consequently, the results of principal component analysis (PCA) showed that MOF and MEF could be separated clearly. In total, 31 chemical markers differentiating MOF and MEF were successfully identified, including 22 flavonoids, 8 isoflavones and 1 benzopyran. Among them, the contents of 18 components, including Calycosin, Cyanidin-3-O-glucoside, Quercetin, Rutin, Kaempferol, Formononetin, Isomucronulatol and Prim-O-glucosylcimifugin in MEF, were significantly higher than in MOF. In turn, the contents of another 13 components, covering Biochanin A, Tectoridin, Isomucronulatol-7-O-glucoside, Liquiritin, Rhamnetin, etc., were lower in the MEF group than that in the MOF group. It is worth noting that flavonoids, especially flavonoid glycosides, were the primary active chemical ingredients in MOF and MEF. The 18 ingredients in MEF with a higher level carried out diverse activities, like anti-oxidant, anti-inflammatory, anti-bacterial and anti-tumor activities, which led us to speculate that MEF may have greater pharmacological effects and potential development prospects than MOF. The present results displayed that the contents of ingredients in the two different species of plants were radically different, and there was significant uniqueness to the components of MOF and MEF. Our study not only provides helpful chemical information for further quality assessment and active mechanism research of MOF and MEF but also offers scientific support for the resource utilization of MOF and MEF.